Inhibition of nSMase2 Reduces the Transfer of Oligomeric α-Synuclein Irrespective of Hypoxia - Sackmann, Valerie; Sinha, Maitrayee Sardar; Sackmann, Christopher; Civitelli, Livia; Bergström, Joakim; Ansell-Schultz, Anna; Hallbeck, Martin (Frontiers in Molecular Neuroscience, 2019)
Recently, extracellular vesicles (EVs), such as exosomes, have been proposed to play an influential role in the cell-to-cell spread of neurodegenerative diseases, including the intercellular transmission of α-synuclein (α-syn). However, the regulation of EV biogenesis and its relation to Parkinson’s disease (PD) is only partially understood. The generation of EVs through the ESCRT-independent pathway depends on the hydrolysis of sphingomyelin by neutral sphingomyelinase 2 (nSMase2) to produce ceramide, which causes the membrane of endosomal multivesicular bodies to bud inwards. nSMase2 is sensitive to oxidative stress, a common process in PD brains; however, little is known about the role of sphingomyelin metabolism in the pathogenesis of PD. This is the first study to show that inhibiting nSMase2 decreases the transfer of oligomeric aggregates of α-syn between neuron-like cells. Furthermore, it reduced the accumulation and aggregation of high molecular weight α-syn. Hypoxia, as a model of oxidative stress, reduced the levels of nSMase2, but not its enzymatic activity, and significantly altered the lipid composition of cells without affecting EV abundance or the transfer of α-syn. These data show that altering sphingolipids can mitigate the spread of α-syn, even under hypoxic conditions, potentially suppressing PD progression.